Peculiarities of titanium implants in patients with long-term absence of teeth and significant atrophy of hard and soft tissues of the jaws - Urakov, Aleksandr; Muhutdinov, Nikita (Medicinski časopis, 2025)
Background/aim: The placement of artificial teeth in case of significant atrophy of hard and soft tissues of the jaws remains one of the most difficult problems in dentistry. The task was set to eliminate the unsolved problems by modernizing the existing methods of transplantation and implantation and analyzing the results of their application in clinical conditions. Materials and methods: In the period from 2002 to 2022, standard surgical dentistry operations of transplantation and implantation were performed in several dental clinics in Russia for 5,280 men and women aged 22 to 85 years. Of these, autogenic bone materials were used in 788 patients, and in 4492 patients, surgical operations were performed with transplantation of xenogenic OsteoBiol biomaterials. All patients were implanted with titanium implants Replace Select (Nobel Biocare, Switzerland). Results: It was shown that transplantation of autogenous bone and xenogenic biomaterials lasted on average about 2.5 and 1.5 hours and resulted in successful engraftment in 83% and 94% of cases (respectively). To exclude accidental perforation of Schneider’s membrane during biomaterial transplantation in conditions of significant maxillary crest atrophy, a method of elevating the floor of the maxillary sinus under illumination with blue light from the nasal cavity was proposed. To improve the aesthetic result when placing the crown on the implant in the conditions of soft tissue deficiency around it the method of transplantation of autogenous material in the form of a round disk with a hole in the center for "dressing" on the implant is proposed. Conclusion: Modern dental technology makes it possible to restore significant defects of soft and bone tissues of the jaws and replace teeth in patients of all age groups.